Pipelines 2013 2013
DOI: 10.1061/9780784413012.034
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Soil-Pipe Friction Coefficients for Coated Steel Pipes

Abstract: Significant thrust forces can be generated on a pressurized pipeline wall or fitting due to internal pressure, momentum forces, surge forces, and/or thermal changes. The produced thrust force can lead to longitudinal movement of a pipeline and its connections. Soil frictional resistance, which is a function of the pipe's surface area and coating material, depth of cover, and soil characteristics, plays a key role in restraining such axial movements. Thus, soil frictional resistance is an important factor in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The results in Fig. 16 show that the friction coefficient decreases with the increase of the normalized buried depth, which is consistent with the finding of Alam et al [15].…”
Section: Effect Of Buried Depthsupporting
confidence: 94%
See 1 more Smart Citation
“…The results in Fig. 16 show that the friction coefficient decreases with the increase of the normalized buried depth, which is consistent with the finding of Alam et al [15].…”
Section: Effect Of Buried Depthsupporting
confidence: 94%
“…In attempting to obtain the friction coefficient of pipelines, theoretical and experimental researches are available. Many researches focused on the interaction of pipe with cohesionless soil over the past several decades [2,[10][11][12][13][14][15]. Only a minority of scholars studied the pipe-clay interaction using model tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is attributed to the sliced bottom face of the topsoil block, where it was flatter for high-moisture soil and crooked for low-moisture soil. The high variation in subsoil was associated with the soil losses during retrieval; larger for low moisture and smaller for high moisture soil (Alam et al 2013). The findings suggested that the lifting and slicing mechanism was effectively operated without adversely affecting the shape and height of the soil blocks.…”
Section: Average Height and Weight Of Soil Blockmentioning
confidence: 91%
“…This study considered a cutting method which is slicing the soil using a cutting blade. The selection of cutting force and mechanism depends on the characteristics of the root system of the plant, soil type, soil moisture level and foreign materials in the soil such as gravel or stones (Alam et al 2013, Jain 2013. The reconstructed soil column used in this study was free of foreign materials like stones and pebbles, easy to slice without deformation for the soil block shape when the soil moisture is high.…”
Section: The Design Consideration For Different Types Of Soilmentioning
confidence: 99%
“…Jung et al (2013) studied the buried pipe response under lateral loads in dry and unsaturated soils using FE modelling and large-scale tests. They found that the lateral loads on pipes in unsaturated conditions were significantly different from Alam et al (2013) Study soil-pipe friction coefficient for different soil types and moisture contents Anderson et al (2005) Evaluate soil-pipe interaction in polyethylene pipelines Shmulevich et al (1986) Study soil stress distribution around buried pipes Tokyo Gas, PERL laboratory experiments (Robert 2010) Study lateral soil load on pipe with different saturations Note: PERL, Pipeline Engineering Research Laboratory.…”
Section: Introductionmentioning
confidence: 99%